Optimum Thickness of Wall Insulations and Their Thermal Performance for Buildings in Malaysian Climate - F., Basrawi; Hassan, Ibrahim; Mohd Yusof, Taib; Lee, Giok Chui (Universiti Malaysia Pahang, 2013)
This study clarifies the optimum thickness of insulation materials for buildings by using the life cycle cost analysis. Common external walls including Clay Brick, Sand Cement Brick and Concrete in Malaysian climate were studied. Various types of buildings including office, residential and hotel were considered. Optimum thickness of insulation materials including Rockwool, Fiberglass and Extruded Polystyrene were clarified. It was found that appropriate insulation thickness in Malaysia is in a range of 18-126 mm. Operating hour and inside-outside temperature difference have significant effect on the life cycle Net Saving. However, different external wall type has slight effect on the life cycle Net Saving. A general index, Cost/k for selecting the most cost effective insulation material was also introduced.